Mental Health Portraits of Adolescents Experiencing Dating Violence - Sugiharto, Jessica Putri; Huwae, Arthur (Bisma The Journal of Counseling, 2025)
Dating violence or violence in dating relationships is a serious problem faced in the context of romantic relationships. This study aims to analyze the mental health of adolescents aged 13-22 years who experience dating violence. Using a descriptive phenomenological research design, this study collected data through in-depth interviews and observations of participants who had experienced various forms of violence in romantic relationships. The number of participants in this study was 6 people. The data collection process in this study used data triangulation, namely interview and observation techniques. The findings show that dating violence has a significant impact on adolescent mental health, which is reflected in increased levels of anxiety, depression, and other emotional disorders. In addition, adolescents involved in such relationships often have difficulty in building healthy social relationships and have negative views of themselves. This study provides important insights into the importance of psychological support and appropriate interventions for adolescents facing similar situations.